Using Continuum-Discontinuum Element Method to Model the Foliation-Affected Fracturing in Rock Brazilian Test - Qunlei Zhang; Zihan Zhi; Chun Feng; Ruixia Li; Jinchao Yue; Junyu Cong (Advances in Civil Engineering)
In this study, the continuum-discontinuum element method (CDEM) was used to investigate the tensile fracture mechanism of rock materials. An isotropic rock disk model and models considering different foliation inclinations were established, and three schemes were used to simulate the rock fracturing in Brazilian test. Then, the influences of the rock matrix and foliation strengths on anisotropy rock fracturing were investigated. Furtherly, simulation results were verified, and the rock fracture mechanisms were discussed. The results show that the rock fracturing in Brazilian test can be accurately simulated by CDEM, which is in accordance with the experimental results. For isotropic and horizontal foliation rock, the stress concentration in loading positions causes a local fracture of rock sample, and application of a local strengthening scheme can simulate the integral tension fracture of sample middle. As the foliation angle varies from 15° to 45°, the rock fracturing is affected by the stress concentration and foliation distribution. In splitting simulation, a strengthening scheme should be adopted to overcome this influence. As a result, the rock sample generates the sliding and compression-shear fracture. As the foliation angle changes from 45° to 75°, the foliation, rather than the matrix, dominates the fracture behavior of rock sample. For vertical foliations’ rock, as the middle foliation thickness is appropriately broadened, the simulation results are reasonable. In general, the tensile strength of anisotropic rock entirely decreases with an increase of foliation angle, and the effect of foliation strength on the tensile strength rock sample is larger than that of the rock matrix.